2019
DOI: 10.1016/j.ijso.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Resident satisfaction regarding surgical training programme in Eastern Saudi Arabia: A cross-sectional study

Abstract: Background: The satisfaction of surgical residents with their training programs is a key indicator for program effectiveness. This survey was conducted to assess the level of perceived satisfaction of surgical residents with the current training programs in Eastern Saudi Arabia. Materials and methods: Resident satisfaction was measured by questionnaire in 119 selected participants at 9 training centers in Eastern Saudi Arabia, as part of the general sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Moreover, the suspension of all deferrable surgeries, with the consequent reduction of daily operational procedures, further contributes to explain this finding [ 11 ]. To outwit this, technology, such as, video-conferencing [ 12 ] and e-learning platforms [ 13 , 14 ], can be used to deliver lectures or tutorials remotely via smartphones, tablets, and laptops. Faculty, residents, and fellows can then log in at designated times for discussions, which can be facilitated in real-time via teleconferencing applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the suspension of all deferrable surgeries, with the consequent reduction of daily operational procedures, further contributes to explain this finding [ 11 ]. To outwit this, technology, such as, video-conferencing [ 12 ] and e-learning platforms [ 13 , 14 ], can be used to deliver lectures or tutorials remotely via smartphones, tablets, and laptops. Faculty, residents, and fellows can then log in at designated times for discussions, which can be facilitated in real-time via teleconferencing applications.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our survey, trainees in Saudi Arabia had their share of this impact in various degrees, leading to mixed feelings and emotional disturbance. Mental illness, behavioral change, and emotional distress are all known to be caused by disaster events [ 14 , 15 ]. Trainee residents and fellows who are based in hospitals and who are in direct contact with suspected or confirmed cases of COVID-19 are the most susceptible to get infected with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The results of dissatisfaction found among residents in our study are in line with the Saudi Board general surgery program residents, as Aldossary et al have reported in a previous study. 4 Their study showed that 44.6% of the studied residents were dissatisfied with their training in the Saudi Board general surgery program. 4 Furthermore, Al Shanafey et al reported that 78% of the Saudi Board surgical residents were dissatisfied with their training as well.…”
Section: Discussionmentioning
confidence: 95%
“…Our study is a nationwide study that investigates the satisfaction level of Saudi Board of Plastic Surgery residents along with the predictors of their satisfaction. The study is the first to assess the satisfaction level of Saudi Board of Plastic Surgery residents since its establishment 4 Their study showed that 44.6% of the studied residents were dissatisfied with their training in the Saudi Board general surgery program. 4 Furthermore, Al Shanafey et al reported that 78% of the Saudi Board surgical residents were dissatisfied with their training as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation